6, 7, 4′-Trihydroxyisoflavone suppressed the estrogen receptor negative breast cancer growth via regulating glycogen synthase kinase-3β/β-catenin signaling. (September 2018) - Chen, Jing; Lee, Jaehoo; Bao, Cheng; Kim, Jin Tae; Lee, Hong Jin
Graphical abstract: Highlights: Daidzein metabolite 6, 7, 4′-THIF inhibited proliferation of breast cancer cells. 6, 7, 4′-THIF arrested G2/M and regulated the related proteins in breast cancer cells. 6, 7, 4′-THIF activated GSK3β and inhibited nuclear β-catenin in breast cancer cells. 6, 7, 4′-THIF inhibited tumor growth and regulated GSK3β/β-catenin in xenograft model. Abstract: The hepatic metabolites of daidzein has been demonstrated to be more potent in chronic diseases than daidzein. However, the investigation of their roles in estrogen receptor (ER)-negative breast cancer is limited. Here, the hepatic metabolite of daidzein 6, 7, 4′-trihydroxyisoflavone inhibited cell proliferation, induced cell cycle arrest at G2/M phase, and regulated the expression of cyclin B, cyclin dependent kinase (CDK)-1 and CDK2 in MCF10DCIS.com ER-negative breast cancer cells. 6, 7, 4′-Trihydroxyisoflavone activated glycogen synthase kinase (GSK)-3β, and suppressed the nuclear translocation of β-catenin. Inhibition of GSK3β by lithium chloride reversed the effect of 6, 7, 4′-trihydroxyisoflavone on β-catenin localization, CDK1, CDK2 and cyclin B expression, and the proliferation of MCF10DCIS.com. In xenograft animal model, 6, 7, 4′-trihydroxyisoflavone inhibited tumor growth, and regulated GSK3β phosphorylation and β-catenin nuclear localization. These results indicate that 6, 7, 4′-trihydroxyisoflavone suppressed ER-negative breast cancer growth through regulating GSK3β/β-catenin signaling, and 6, 7, 4′-trihydroxyisoflavone may be a potent chemopreventive agent in regulating the ER-negative human mammary carcinogenesis.